Weiterführende statistische Methoden für Politikwissenschaftler : Eine anwendungsbezogene Einführung mit Stata. - Wenzelburger, Georg (Politikwissenschaft kompakt., 2014)
This book provides a practical introduction to advanced techniques of regression analysis for political scientists. Building upon detailed discussion of the fundamentals of regression analysis, it individually presents the advanced techniques of regression analysis. The textbook aims to impart an understanding of the underlying operating principles of advanced analytic techniques, and about their advantages and drawbacks.